Benchmarking Analysis of Road Safety Levels for an Extensive and Representative Dataset of European Cities - Folla, Katerina; Nikolaou, Paraskevas; Dimitriou, Loukas; Yannis, George (My University, 2021)
According to European urban sustainable planning guidelines, road safety corresponds to one of the most important elements of cities’ performance. Several methods have been developed over the years for supporting policy-making, towards the improvement of road safety levels mainly at the national level. In this study, a methodological framework is developed, extending the macro-level (national) analysis and focusing at a higher spatial resolution, that of urban regions. The methodological approach is based on benchmarking analysis, able to suitably rank alternative cases/regions with distinctive characteristics within a multivariate comparative framework and on the investigation of the components that affect their ranking. In particular, an extensive and representative dataset from 101 European regions is collected and analyzed, incorporating their socio-economic, demographic and road infrastructure characteristics. Then, Data Envelopment Analysis (suitably adapted to road fatalities framework) has been developed, evaluating the urban regions’ road safety performance over a period of 9 years. The resulted region ranking is further examined by using Tobit regression models for identifying the components that appear to affect their performance in different extents providing a valuable guiding ‘tool’ for experience/knowledge-transfer and policy-making. The datasets and the results are presented and discussed in detail, such as they will be useful not only for demonstration purposes but also they will be suitable as a benchmark for researchers and practitioners.
Keywords: Benchmarking analysis; Sustainable urban mobility; Road traffic fatalities; Stochastic frontier; Data Envelopment Analysis